IgG Suppresses Antibody Responses to Sheep Red Blood Cells in Double Knock-Out Mice Lacking Complement Factor C3 and Activating Fcγ-Receptors - Anania, Jessica C.; Westin, Annika; Heyman, Birgitta (Frontiers in Immunology, 2020)
Antigen-specific IgG antibodies, passively administered together with erythrocytes, prevent antibody responses against the erythrocytes. The mechanism behind the suppressive ability of IgG has been the subject of intensive studies, yet there is no consensus as to how it works. An important question is whether the Fc-region of IgG is required. Several laboratories have shown that IgG suppresses equally well in wildtype mice and mice lacking the inhibitory FcγIIB, activating FcγRs (FcγRI, III, and IV), or complement factor C3. These observations consistently suggest that IgG-mediated suppression does not rely on Fc-mediated antibody functions. However, it was recently shown that anti-KEL sera failed to suppress antibody responses to KEL-expressing transgenic mouse erythrocytes in double knock-out mice lacking both activating FcγRs and C3. Yet, in the same study, antibody-mediated suppression worked well in each single knock-out strain. This unexpected observation suggested Fc-dependence of IgG-mediated suppression and prompted us to investigate the issue in the classical experimental model using sheep red blood cells (SRBC) as antigen. SRBC alone or IgG anti-SRBC together with SRBC was administered to wildtype and double knock-out mice lacking C3 and activating FcγRs. IgG efficiently suppressed the IgM and IgG anti-SRBC responses in both mouse strains, thus supporting previous observations that suppression in this model is Fc-independent.